Chlorpromazine activates cGAS-STING signaling and reprograms the immune response in glioblastoma - Fanelli, Giulia; Gesualdi, Luisa; Ascione, Barbara; Paolini, Francesca; Gambardella, Lucrezia; Sacconi, Andrea; Paggi, Marco G.; Matarrese, Paola; Abbruzzese, Claudia (Frontiers in Immunology, 2026)
BackgroundGlioblastoma (GBM), the most common and aggressive primary brain tumor in adults, poses a formidable therapeutic challenge, due to its intrinsic radio- and chemoresistance and its ability to create a hostile, immunosuppressive tumor microenvironment (TME). Drug repurposing has emerged as a promising strategy to fight GBM. In this context, our efforts focused on chlorpromazine (CPZ), a first-generation antipsychotic agent previously shown by us to exert anti-tumor effects in both preclinical and clinical settings.MethodsWe investigated the role of CPZ in remodeling the GBM microenvironment and shaping immune responses using four GBM cell lines, two standard anchorage-dependent models and two patient-derived neurospheres, enriched for tumoral stem cells. We determined cGAS-STING pathway activation and downstream gene expression via flow cytometry and RT-PCR. The cellular secretome following drug treatment was profiled via a luminescence cytokinome assay using a panel of 27 chemokines. Macrophages were phenotyped by flow cytometry using M1 and/or M2 specific markers and, finally, PD-L1 expression was assessed by quantitative flow cytometry and immunoblot analysis.ResultsWe demonstrate that CPZ, alone or in combination with temozolomide (TMZ), the current standard of care, activates the cGAS-STING signaling pathway, thus promoting anti-tumor immune responses. Importantly, CPZ counteracts the immunosuppressive effects of TMZ, hindering some TMZ-induced processes as: i) induction of tumorigenic cytokines; ii) macrophage polarization toward a tumor-supportive M2-like phenotype, and iii) increase of PD-L1 expression, a key mechanism of immune evasion.ConclusionsThis study uncovers that CPZ exerts a previously unrecognized anti-cancer immunomodulatory activity, remodeling the immune microenvironment and enhancing the anti-tumor immune response. By overcoming TMZ resistance, CPZ not only exerts a direct anti-neoplastic effect, but also sensitizes GBM cells to standard therapy.